Highlights from the clinical trials in organ transplantation (CTOT)‐20 and CTOT‐22 Consortium studies in lung transplant. Issue 6 (29th May 2020) - Snyder, Laurie D.; Belperio, John; Budev, Marie; Frankel, Courtney; Kirchner, Jerry; Martinu, Tereza; Neely, Megan L.; Reynolds, John M.; Shah, Pali; Singer, Lianne G.; Todd, Jamie L.; Tsuang, Wayne; et al.
Abstract : Long‐term survival after lung transplant lags behind that of other commonly transplanted organs, reflecting the current incomplete understanding of the mechanisms involved in the development of posttransplant lung injury, rejection, infection, and chronic allograft dysfunction. To address this unmet need, 2 ongoing National Institute of Allergy and Infectious Disease funded studies through the Clinical Trials in Organ Transplant Consortium (CTOT) CTOT‐20 and CTOT‐22 were dedicated to understanding the clinical factors and biological mechanisms that drive chronic lung allograft dysfunction and those that maintain cytomegalovirus polyfunctional protective immunity. The CTOT‐20 and CTOT‐22 studies enrolled 800 lung transplant recipients at 5 North American centers over 3 years. Given the number and complexity of subjects included, CTOT‐20 and CTOT‐22 utilized innovative data transfers and capitalized on patient‐entered data collection to minimize site manual data entry. The data were coupled with an extensive biosample collection strategy that included DNA, RNA, plasma, serum, bronchoalveolar lavage fluid, and bronchoalveolar lavage cell pellet. This Special Article describes the CTOT‐20 and CTOT‐22 protocols, data and biosample strategy, initial results, and lessons learned through study execution. Abstract : This Special Article describes how the Clinical Trials in Organ Transplant (CTOT) CTOT‐20 and CTOT‐22 studies utilized innovative data collection and transfers, patient entered data, and an extensive biosample collection strategy to understand the clinical factors and biological mechanisms that drive chronic lung allograft dysfunction and identify cytomegalovirus polyfunctional protective immunity.